TINJAUAN TENTANG SISTEM PENDINGINAN ADSORPSI SURYA - Rachman, Arfidian; Dewi, Arfita Yuana; Effendi, Asnal (ITP Press, 2025)
The primary aim of this paper is to offer key insights into solar energy and waste heat adsorption cooling systems, as well as to present a helpful approach concerning the design aspects of the adsorbent bed utilized in adsorption cooling. In recent decades, solar-powered water purifiers have primarily been utilized for heating water in residential settings. In contrast, solar cooling systems have mainly been designed for demonstration purposes. It indicates that absorption cooling systems are better suited for large buildings, while adsorption cooling systems show greater promise for smaller air conditioning units. It is advised to plan solar-powered systems in public facilities. Highly efficient heat pumps are regarded as the best supplementary heat providers since they can operate independently of weather conditions.